Counseling: alternative to increase self-responsibility and self-efficacy before COVID-19 - Laura Magda López Angulo; Anais Marta Valladares González (Medisur)
WHO considers that counseling is the technique par excellence to face the problem of communicable diseases due to its great potential as a means of providing personal support and because of the possibilities it offers for behavior modification. Other health problems can also benefit from the accumulated experiences in counseling. This work aims at proposing a methodology for Counseling Services to people in epidemiological surveillance and patients of COVID -19.